Small ruminant production under pressure: The example of goats in southeast Nigeria - Mack, S.; Sumberg, J.E.; Okali, C. (International Livestock Centre for Africa, 1984)
Presents preliminary assessment of animals' performance under a free-roaming and movement-restricted production system and farmers' responses to changed husbandry practices in southeast Nigeria; with particular reference to flock dynamics & male to female ratio; reproductive performance; growth rate; mortality; and farmers management & breeding strategy.